2003
DOI: 10.1139/b03-034
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium verticillioides induction of maize seed rot and its control

Abstract: Experimental evidence is lacking to demonstrate whether Fusarium verticillioides (synonym = Fusarium moniliforme J. Sheld.; teleomorph = Gibberella fujikuroi (Sawada) Ito in Ito & K. Kimura, mating population A) functions as a causative agent or an opportunistic invader in seed (caryopsis) rot of maize (Zea mays L.). Previous researchers have isolated this fungus, along with many other microorganisms, from seed collected in the field long after rot commenced. The current investigations used an isolate of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Previous researchers determined that F. verticillioides can function as the causative agent of maize seed rot (Yates et al 2003). However, we found that all maize plants grown from seeds inoculated with F. verticillioides (10 7 spores ml -1 ) and with the BCAs, B. amyloliquefaciens (T3) and M. oleovorans (T4) at 10 9 CFU ml -1 , grew well and did not show symptoms of disease after 20 days of cultivation in pots.…”
Section: Discussionmentioning
confidence: 62%
“…Previous researchers determined that F. verticillioides can function as the causative agent of maize seed rot (Yates et al 2003). However, we found that all maize plants grown from seeds inoculated with F. verticillioides (10 7 spores ml -1 ) and with the BCAs, B. amyloliquefaciens (T3) and M. oleovorans (T4) at 10 9 CFU ml -1 , grew well and did not show symptoms of disease after 20 days of cultivation in pots.…”
Section: Discussionmentioning
confidence: 62%
“…include wilts, rots, cankers, and blights of numerous agronomic, horticultural, and forest plants grown in agricultural, landscape, and natural settings (19). F. verticillioides causes ear rot of maize and sorghum (20) and Pokkah Boeng disease of sugarcane (21). Members of the F. oxysporum species complex cause wilt diseases of more than one hundred plant species (19).…”
mentioning
confidence: 99%
“…Diseases caused by these Fusarium spp. are difficult to control with existing fungicides or soil fumigants, and many agricultural plants lack resistance to them (20,22). To meet the need for alternative disease management strategies, scientists have turned to microorganisms that inhibit Fusarium spp.…”
mentioning
confidence: 99%
“…In the upfield portion of the 1 H NMR spectrum of 1, the sp 3 methylene proton resonances comprised a broad signal at δ 1.20-1.30, integrating for 10H, a distorted triplet (J ) 7.0 Hz) for 2H at δ 2.81, a quintuplet (J ) 7.0 Hz) for 2H at δ 1.68, and a distorted quartet (J ) 7.0 Hz) for 2H at δ 2.07. A terminal double bond was identified by the signals from the three spin system at δ 5.86 (1H, ddt, J ) 17.2, 10.1, 7.0 Hz), 4.92 (1H, dtd, J ) 17.2, 1.8, 1.5 Hz), and 5.02 (1H, dtd, J ) 10.1, 1.8, 1.5 Hz), while two quaternary carbons at δ 183.3 and 104.7 in the 13 C NMR spectrum were attributed to an enol moiety.…”
mentioning
confidence: 99%
“…To have larger amounts for biological tests, compound 2 was synthesized in 16% yield by condensation of 4-cyclopentene-1,3-dione with undecanoyl chloride in the presence of excess anhydrous AlCl 3 .…”
mentioning
confidence: 99%